Fatal Necrotizing Fasciitis Following Uncomplicated Colonoscopic Polypectomy: A Case Report - Min Kyu Chae; Sang Youn Shin; Min Seob Kwak; Jin Young Yoon; Ha Il Kim; Jae Myung Cha (Korean Society of Gastrointestinal Endoscopy, 2021)
Necrotizing fasciitis (NF) is a life-threatening infection that can be caused by various procedures or surgery and may develop in healthy elderly patients. Here, we report a case of a 66-year-old man with diabetes mellitus who underwent colonoscopic polypectomy, without complications. However, he visited the emergency department 24 hours after the procedure complaining of abdominal pain. Abdominopelvic computed tomography revealed multiple air bubbles in the right lateral abdominal muscles. After a diagnosis of NF was made, immediate surgical debridement was performed. However, despite three sessions of extensive surgical debridement and best supportive care at the intensive care unit, the patient died because of sepsis and NF-associated multiple-organ failure. In conclusion, physicians should pay special attention to the possibility of NF if a patient with risk factors for NF develops sepsis after colonoscopic polypectomy.